Aru Shah and the end of time : the graphic novel - Caramagna, Joe ([Pandava graphic novels], 2022)
Twelve-year-old Aru stretches the truth to fit in at her private school, but when she is dared to prove an ancient lamp is cursed, she inadvertently frees an ancient demon.